Diversity Concerns between China and Pakistan and its Impact on CPEC Success and Sustainability (KASBIT Business Journal, 2019)
This study focuses on the concerns of diversity between China and Pakistan and issue which might be impact on the CPEC sustainability and success due to these diversities. As far as the concerns for the diversity among both nations this study focuses particularly on political diversity, socio-cultural diversity and economic diversity. Many researchers and scholars finding way out towards theses diversity challenges; this study helps in finding solution for the diversity problem to cater it well before time. This study also helps the way to converge the Diversity where the situation is feasible for both nations. This is review based study which proposes an integrated model with the help of inductive reasoning. The suggested theory of the study states that if the diversity concerns among both countries reduce or eliminate or converge in one place; it leads to CPEC success and sustainability. This is a partial work which will be empirically tested in next study with the help of quantitative survey, data analysis and findings. This study primarily focuses on these research objectives: 1. To highlight and review the diversity between two societies; China and Pakistan.2. To suggest the way forward in resolution to the expected diversity issues between both nationals and provide the way towards sustainability and success of CPEC project. 3. To determine the feasible solutions towards the convergence of culture and diversity to both countries. Practical implication of this paper will be served as an eye-opening issue for strategic decision making of CPEC to converge two different country’s diversity in one place for optimization and project success.
Keywords: CPEC; OBOR; China and Pakistan; CPEC success and sustainability; diversity concerns; political diversity; economic diversity; socio-culture diversity